Analisis dan Perancangan Antarmuka Pengguna Situs Web PT. ACW Tour dan Travel Menggunakan Metode Design Thinking - Rezeki Bertuah Sikumbang; Fadli Suandi; Maidel Fani (Politeknik Negeri Batam, 2025)
PT. ACW Tour and Travel is a company engaged in the field of tourism services that still uses traditional promotion methods. This study aims to design the UI/UX of the PT. ACW Tour and Travel website using the Design Thinking approach, in order to provide a better user experience and support digital marketing strategies. The design process includes five stages, namely empathize, define, ideate, prototype, and test. Data were collected through interviews and questionnaires to potential users. The final result is a website prototype design that was tested using the System Usability Scale (SUS) method with an average score of 77.3, which is categorized as